Contrasting continental patterns of adaptive population divergence in the holarctic ectomycorrhizal fungus Boletus edulis. Issue 1 (17th November 2022) - Tremble, Keaton; Hoffman, J. I.; Dentinger, Bryn T. M.
Summary: In the hyperdiverse fungi, the process of speciation is virtually unknown, including for the > 20 000 species of ectomycorrhizal mutualists. To understand this process, we investigated patterns of genome‐wide differentiation in the ectomycorrhizal porcini mushroom, Boletus edulis, a globally distributed species complex with broad ecological amplitude. By whole‐genome sequencing 160 individuals from across the Northern Hemisphere, we genotyped 792 923 single nucleotide polymorphisms to characterize patterns of genome‐wide differentiation and to identify the adaptive processes shaping global population structure. We show that B. edulis exhibits contrasting patterns of genomic divergence between continents, with multiple lineages present across North America, while a single lineage dominates Europe. These geographical lineages are inferred to have diverged 1.62–2.66 million years ago, during a period of climatic upheaval and the onset of glaciation in the Pliocene–Pleistocene boundary. High levels of genomic differentiation were observed among lineages despite evidence of substantial and ongoing introgression. Genome scans, demographic inference, and ecological niche models suggest that genomic differentiation is maintained by environmental adaptation, not physical isolation. Our study uncovers striking patterns of genome‐wide differentiation on a global scale and emphasizes the importance of local adaptation and ecologically mediated divergence, rather than prezygotic barriers such as allopatry or genomic incompatibility, in fungal population differentiation.